Application of remote sensing on the dispersion and concentration of total suspended sediment offshore Langat Estuary - Othman , A; Karim Othman Jaafar; Sharifah Mastura Syed Abdullah (Universiti Kebangsaan Malaysia, 2004)
This paper focuses on Langat River basin which is experiencing fast pace land use changes and accelerated soil erosion associated with land clearing and earthwork activities. Land use changes detected from Landsat imageries from 1989-1999 show that urban expansion is the most active, i.e. recording an expansion of 180% over that time period. The major land use reduction is the tropical dipterocarp rainforest located along the upper catchment of the Langat River and the mangrove forest found along Kuala Langat in the west. The 11% decline in the trend of the forest over that decade is anticipated to contribute in the near future. Results from logistic regression on the casual factors of rapid land use changes are attributed to three significant variables namely transport accessibility, population dynamics and agriculture. The eroded material due to land use changes enters into the Langat River systems as suspended sediments and contributed as non point source of pollution. Some finer sediment is being discharged offshore forming sediment plumes at the river estuary. Sediment plumes detected by Landsat TM imageries were analysed. It is found that the dispersion was not extensive and generally the suspended solids existed at low concentration (varying from 10-50 mg/l). This result is unexpected considering the rapid land use and land cover change that is occurring within the basins. These are mainly due to the loss of sediments during flooding into flood plain and active dredging of the river channels.